SURVEY ON OUTDOOR AIRBORNE FUNGAL SPORES OF TUMKUR CITY, KARNATAKA STATE, INDIA - K.L. RAVIKALA; K.V. NAGALAKSHAMMA (International Journal of Pharma and Bio Sciences, 2016)
The present study was carried out to investigate the outdoor airborne fungal spore genera circulating in the 5 different sites situated at Tumkur city, Karnataka state, India. Sampling was carried out by Andersen two stage sampler using a Malt Extract Agar (MEA) media were collected fortnightly from January to June, 2015. A total of 2326.11 CFU/m3 airborne fungi recorded. The most common airborne fungal spores in outdoor environment were Aspergillus sp., Aspergillus niger, Alternaria sp., Alternaria alternata, Cladosporium sp., Cladosporium herbarum, C. cladosporioides, Curvularia sp, Fusarium sp., Mucor sp, Nigrospora sp, Penicillium sp, Rhizopus sp, Trichoderma species and 1 unidentified genera species were observed. The present study helped to determine the airborne fungal spore genera and types present in the atmosphere of 5 different sites, which may useful for physician to identify the cause of fungal spores related problem affecting the human health and environmental sustainability.